2010
DOI: 10.1137/090778055
|View full text |Cite
|
Sign up to set email alerts
|

Exact and Efficient Simulation of Correlated Defaults

Abstract: Abstract. Correlated default risk plays a significant role in financial markets. Dynamic intensity-based models, in which a firm default is governed by a stochastic intensity process, are widely used to model correlated default risk. The computations in these models can be performed by Monte Carlo simulation. The standard simulation method, which requires the discretization of the intensity process, leads to biased simulation estimators. The magnitude of the bias is often hard to quantify. This paper develops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 58 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…For future work, we will study how to estimate sensitivities when the joint defaults are modeled using frailty models or self excited models, which are closely related to doubly stochastic models but are capable of capturing default clustering effects (see, for instance Giesecke et al 2010 for a thorough introduction of these models). In these models, the intensity function may not be continuous with respect to the parameter that we want to consider.…”
Section: Discussionmentioning
confidence: 99%
“…For future work, we will study how to estimate sensitivities when the joint defaults are modeled using frailty models or self excited models, which are closely related to doubly stochastic models but are capable of capturing default clustering effects (see, for instance Giesecke et al 2010 for a thorough introduction of these models). In these models, the intensity function may not be continuous with respect to the parameter that we want to consider.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to estimate the accurate probabilities within a reasonable computational time, we embed IPS to original standard Monte Carlo simulation algorithm. In the following two subsections, we provide a quick overview of the IPS inspired by the pioneering work Del Moral and Garnier [15] and subsequent papers Carmona, Forque and Vestal [14], Carmona and Crepey [16] and Giesecke et al [7].…”
Section: Interacting Particle Systemmentioning
confidence: 99%
“…Since the contagion effects heavily influence the correlations of defaults, capturing them in quantitative models is crucial. Existing dynamic credit risk models which deal with default contagion include, among others, Davis and Lo [1], Fan Yu [2], Frey and Backhaus [3], Frey and Runggaldier [4], Giesecke [5], Giesecke and Goldberg [6], Giesecke et al [7], Schönbucher [8], Takada and Sumita [9] and comprehensive surveys can be found in Chapter 9 of McNeil, Frey and Embrechts [10]. Generally, credit risk modeling methodologies are categorized to either reduced form approach or structural approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Already several papers [3,8] appeared after the first version of this paper was first circulated. They show the strength of IPS-based Monte Carlo computations of small default probabilities, especially when other methods fail.…”
Section: Introductionmentioning
confidence: 99%